Sorption Properties of Ordered Mesoporous Silica for Toluene and Ethyl Acetate - Weiyang Jin; Yuejuan Wang; Xueli Wang; Lingyun Jin; Jiqing Lu; Mengfei Luo (Adsorption Science & Technology)
The sorption properties of SBA-15 and MCM-41 for toluene and ethyl acetate were investigated by temperature programmed desorption (TPD) techniques and an analysis of breakthrough curves. The amount of toluene adsorbed onto SBA-15 was distinctly larger than that onto MCM-41, while the desorption temperature of toluene from the former was also higher than that from MCM-41. However, in the case of ethyl acetate, similar adsorption and desorption behaviours were observed on these two samples. The interaction between organic molecules and adsorbents was evaluated in terms of the affinity index. It was found that both SBA-15 and MCM-41 exhibited positive adsorption properties towards ethyl acetate but negative behaviours towards toluene. Compared to the MCM-41, the larger quantity of toluene retained by SBA-15 and the higher desorption temperature for toluene relative to MCM-41 were ascribed to the higher adsorption potential existing in the secondary pores of SBA-15.